Pemberdayaan Potensi Masyarakat pada Pengembangan Platform Edukasi Content Creator Berbasis E-Learning - Alif Ringga Persada; Bayu Sukmaangara (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
EMPOWERING COMMUNITY POTENTIAL IN DEVELOPING AN E-LEARNING BASED CONTENT CREATOR EDUCATION PLATFORM. This service activity aims to empower potential in developing an e-learning based content creator educational platform for academics and the community driving education and vocational skills in Cirebon City. In implementing this community service, the Assest Based Community Development (ABCD) method is used. The result of this activity is that academics and the education community gain a better understanding of the terms Content Creator and Digital Marketing. They can prepare curriculum and materials about Content Creator which are implemented in the form of book modules and learning videos on the Learning Management System (LMS) Platform called TEKAD (Talent Digital Academy). This training produced a product in the form of a TEKAD book module which has been published and provided as teaching material, as well as a product in the form of a learning video about content creators in the TEKAD pratform.